Microrede industrial em corrente contínua, uma oportunidade atraente para eficiência energética - Guedes, Aderaldo Ricarte (2018)
This work presents a direct current (DC) bus topology for industrial use that allows energy recovery from motor braking and the application of supercapacitors for energy storage. Aspects of the energy efficiency assessment are also evaluated with the use of Permanent Magnet Synchronous Motors (PMSM) in the industry, in particularly applied to plastic injection machine, replacing three–phase induction motors (TPIM). The possibility of removing the bidirectional converter used as interface between the DC bus and the supercapacitor will be discussed. Unlike a traditional microgrid, which voltages have fixed values, this work will address the voltage variations that the DC bus in the industry can suffer due to motor braking and high energy recovery in a short period of time. Using of recovery and storage systems with supercapacitors, new standards for DC voltage levels in the industry must be adopted and two–way rectifiers can be left aside, since the regenerated energy will be stored and used for start another machine or the energy will be consumed by another machine which will start at same time. This work presents experimental results that demonstrate the PMSM was able to save 28% more energy than MIT and energy regeneration of the engine braking allowed to save 5.05% of electric energy in a injection molding machine (GEK 280/S).